The Development of an IoT-Based Palm Solid Waste Counting System for Empty Fruit Bunches in the Palm Oil Industry - Siregar, Emil Salim Parhimpunan; Mirnandaulia, Meutia; Hutajulu, Poltak Evencus; Hidayani, Tengku Rachmi; Marbun, New Vita Mey Dessty; Rachmiadji, Irwan; Hikmawan, Oksya; Hariyanto, Hariyanto; Tarigan, Enda Rasilta Br.; Simanjuntak, Andreas Rumata; Falah, Miftahul; Pardede, Erwin; Donda, Donda; Sitepu, Evi Christiani (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The recent application of palm empty fruit bunches as solid waste directly on soil or as organic fertilizer has enhanced palm farms. Moreover, the co-products of this palm oil mill constitute a dependable metric for assessing mill processing performance, specifically regarding quantity and weight. The quantity of palm empty fruit bunches is usually ascertained through manual counting using a hand counter during processing. The imprecision in calculating palm empty fruit bunches is a limitation of this method, as operators sometimes perform erroneous calculations, overlook quantities, and produce contradictory results for mill management. To address this issue, the sector requires enhanced execution of a monitoring and counting system methodology. The aim of this community service project is to create an empty fruit bunches count station using an IoTbased palm solid waste counting system for use in palm mills. The Ministry of Industry - Politeknik Teknologi Kimia Industri (PTKI) Medan will engage in and oversee the advancement of Industry 4.0 within the industrial sector. The initiative was executed at Tanah Gambus Estate in Batubara Regency, North Sumatra. Assistance was provided by a palm mill partner associated with PT. Socfin Indonesia. The implementation of the empty fruit bunches palm oil counting system was conducted efficiently, facilitating optimal operations, real–time online monitoring, uninterrupted functionality exceeding 24 hours daily, swift assessment of the empty fruit bunches volume, immediate identification of traditional counting inaccuracies by operators and management, and its station provides benefits to the palm industry.